Damage and failure mode maps of composite sandwich panel subjected to quasi-static indentation and low velocity impact - Zhu, Shengqing; Chai, Gin Boay (Composite structures, 2013)
In this contribution, modes of damage and modes of failure of composite sandwich panel subject to quasi-static indentation and low velocity impact were investigated. This study was conducted through the use of the finite element analysis, existing formulae and experiments. The damage and failure modes of composite sandwich panels were analyzed with some deliberation. With these results, damage and failure mode maps were compiled to facilitate the design of composite sandwich structures. Existing formulae that predict limit loads for damage modes which includes matrix shear/tension damage and core buckling, were reviewed and compiled to plot the damage mode map. The failure modes of facesheet cracking, overall core crushing and core shear fracture, were investigated to configure the failure mode map. Preferred damage and failure modes for impact resistance were also discussed in term of energy absorption. Extensive quasi-static indentation and low-velocity impact tests were carried out to verify these modes. The results of the finite element analysis are also included to complement the work reported in this contribution.